Effectiveness of Schema Mode Therapy on Ambivalence in Emotional Expression and Defense Styles in Individuals with Narcissistic Personality Disorder - Gholami, Mohammad; Maredpour , Alireza; Zadehbagheri, Ghader; Gholami , Fatemeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: Objective: This study aimed to investigate the effectiveness of schema mode therapy on ambivalence in emotional expression and defense styles in individuals with narcissistic personality disorder. Methods and Materials: This semi-experimental study employed a pretest-posttest design with a control group and follow-up. The statistical population consisted of individuals with narcissistic personality disorder who referred to counseling centers in Shiraz during 2023-2024. A total of 60 participants were selected through convenience sampling and randomly assigned to an experimental group (30) and a control group (30). The research instruments included the Emotional Expressivity Questionnaire (EEQ), the Defense Style Questionnaire (DSQ-40), and structured clinical interviews. The experimental group underwent 12 weekly 90-minute sessions of schema mode therapy, while the control group received no intervention. Data were analyzed using covariance analysis and Bonferroni post hoc tests. Findings: The results indicated that schema mode therapy significantly increased positive emotional expression and intimacy while decreasing negative emotional expression in the experimental group (P<0.01). Additionally, a significant increase in mature defense styles and a reduction in neurotic and immature defense styles were observed in the experimental group (P<0.01). Conclusion: Schema mode therapy is an effective approach for improving emotional expression ambivalence and transitioning from maladaptive to adaptive defense styles. This therapeutic method can be considered a suitable clinical intervention for individuals with narcissistic personality disorder.